EVALUASI DAN SUPERVISI PROGRAM BIMBINGAN DAN KONSELING PADA JENJANG SMP, SMA DAN SMK DI PESANTREN ‘X’ KABUPATEN SITUBONDO - Hanik Mufaridah; Ach. Zukin (Konseling At-Tawazun, 2023)
Evaluation and supervision of the counseling program in schools is very important, because it can provide feedback to counselors to improve or (counselor supervisors) develop guidance and counseling programs. This research uses a qualitative approach with a descriptive type. The results of the study show that the evaluation of the guidance and counseling service program made by the guidance and counseling teacher (BK teacher) refers to comprehensive guidance and counseling which includes basic services, individual planning services, responsive services and system support. However, in its implementation, it is more focused on the problem of scores of violations committed by students. In addition, the lack of understanding of counseling teachers in counseling is due to the large number of counseling teachers with non-BK backgrounds. On the other hand, the number of students supervised by each counseling teacher exceeds the ratio of 1:150 students, so the services provided are less than optimal. Whereas in terms of supervision, the supervisors have not been maximal in carrying out supervision because the educational background is not guidance and counseling. In addition, supervision is carried out for all subject teachers in each institution.